Taurine in Sports: Impact on Athletic Performance, Muscle Recovery and Neurological Function in Athletes – A Narrative Review - Jezierski, Michał; Brynczka, Izabela; Patrzykąt, Klaudia Martyna; Gorzoch-Burduk, Zofia; Puzio, Julia; Marcinkowska, Paula; Krzyżaniak, Marta; Popielarska, Kinga; Nowicka, Ewelina; Wróblewska, Kamila (Quality in Sport, 2025)
*:first-child]:mt-0" style="font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none; caret-color: #000000; color: #000000;"> *:first-child]:mt-0" style="font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none; caret-color: #000000; color: #000000;"> Purpose: This review examines the ergogenic potential of taurine in athletes, focusing on its effects on aerobic and anaerobic performance, exercise-induced muscle damage (EIMD), recovery, and neurological aspects such as pain perception and cognitive focus. It also considers how dose, timing, and duration (acute vs. chronic use) influence outcomes. Materials and Methods: A narrative review of 19 peer-reviewed studies (RCTs, meta-analyses, observational research) from PubMed, Scopus, and Google Scholar was conducted. Studies involved swimming, running, cycling, speed skating, and resistance training. Taurine doses ranged from 0.05–6 g/day. Outcomes included VO2max, time to exhaustion, time-trial performance, anaerobic power (Wingate, vertical jump), biomarkers of muscle damage (CK, LDH), oxidative stress (MDA, SOD, GSH), pain, and RPE. Results: Effects varied by exercise type and dosing. In anaerobic tasks, acute taurine (6 g) enhanced peak and mean power and lowered RPE in elite athletes, while broader data indicate improved vertical jump. Endurance results were inconsistent: some studies showed no changes in VO2max or time-trial performance, whereas others reported increased time to exhaustion and greater lipid use. Taurine consistently reduced CK, LDH, and MDA after exercise, especially 24–48 hours post-effort. It also affected pain perception up to 96 hours and showed neuroprotective properties in animal models. Conclusions: Taurine is a safe option for reducing EIMD and oxidative stress, supporting recovery. Ergogenic benefits appear stronger in anaerobic, high-power activities than in endurance sports, where outcomes are mixed and may relate to non-responder effects in elite athletes. Taurine’s influence on lipid metabolism and lactate kinetics suggests support for anaerobic energy processes. Further research should refine dosing strategies and explore neuroprotective roles in contact sports.